2009
DOI: 10.1111/j.1439-0272.1998.tb01380.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of very high doses of human growth hormone (hGH) on the male reproductive system in the dog

Abstract: Summary. The effects of very high doses of human growth hormone (hGH), pituitary derived or recombinant methionyl‐hGH, on the morphology of reproductive organs and on some hormones in the male dog are described. The studies were part of a toxicological documentation of hGH. A total of 18 male dogs aged 7.5–20.5 months, from four studies were treated subcutaneously with hGH for 20–28 days at dose levels of 3, 10 or 25 IU kg−1 day−1 or 1 IU kg−1 three times weekly. Plasma levels of luteinizing hormone (LH), tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In the latter situation, it could be that GH-mediated enhancement of aromatase activity leads to an increase in testosterone to E2 conversion, reducing testosterone levels but increasing E2 (72, 88). However, administration of GH and subsequent GH-mediated effects were found to be dose dependent, as high concentrations given to GH-deprived canines caused atrophy of testes and accessory organs, thinning of prostatic epithelium and a reduction in LH and testosterone levels (75). In addition, overexpression of GH in mice led to early testicular aging characterized by lower expression of the androgen receptor (AR) and LHR (77).…”
Section: Role Of Gh In Testesmentioning
confidence: 99%
“…In the latter situation, it could be that GH-mediated enhancement of aromatase activity leads to an increase in testosterone to E2 conversion, reducing testosterone levels but increasing E2 (72, 88). However, administration of GH and subsequent GH-mediated effects were found to be dose dependent, as high concentrations given to GH-deprived canines caused atrophy of testes and accessory organs, thinning of prostatic epithelium and a reduction in LH and testosterone levels (75). In addition, overexpression of GH in mice led to early testicular aging characterized by lower expression of the androgen receptor (AR) and LHR (77).…”
Section: Role Of Gh In Testesmentioning
confidence: 99%
“…While Lindgren et al [ 61 ] observed normal testicular development in boys with GH deficiency or idiopathic short stature regardless of GH treatment status, a newer study observed increased testicular volume in GH-treated short children associated with a longer pubertal duration [ 49 ]. High-dose GH treatment of GH-replete animals conversely induces atrophy of the testes and accessory organs in dogs [ 62 ] and has no effect on testicular volume in monkeys [ 63 ]. Overexpression of the GH transgene similarly impairs testicular development (reviewed by [ 2 ]); thus, testicular actions of GH, like many other actions, appear to be biphasic.…”
Section: Male Fertilitymentioning
confidence: 99%
“…In this study, the testis weights of rhGH rats were lower than those of control rats on PND 24, although that difference was mitigated on PND 31. Similarly, in immature male dogs, a high dose of rhGH induced atrophy of the testes and accessory organs [ 30 ]. GH can induce apoptosis and atretic changes in the ovaries and testes of mammals, including humans, by activating the PI3K-Akt pathway [ 31 ].…”
Section: Discussionmentioning
confidence: 99%